An Increase in Vigorous but Not Moderate Physical Activity Makes People Feel They Have Changed Their Behavior - Szymczak, Hermann; Keller, Lucas; Debbeler, Luka J.; Kollmann, Josianne; Lages, Nadine C.; Gollwitzer, Peter M.; Schupp, Harald T.; Renner, Britta (Frontiers in Psychology, 2020)
Objective: While behavioral recommendations regarding physical activity commonly focus on reaching demanding goals by proposing ‘thresholds’, little attention has been paid to the question of how much of a behavioral change is needed to make people feel that they have changed. The present research investigated this relation between actual and felt behavior change. Design: Using data from two longitudinal community samples, Study 1 and 2 comprised 614 (63 % women) and 398 participants (61 % women) with a mean age of 40.9 years (SD = 13.6) and 42.5 years (SD = 13.4), respectively. Using a stage-approach, participants were classified into four groups by asking them at the respective second measurement to indicate whether they had become more physically active since their last participation six months ago (“Changers”), had tried but did not succeed in becoming more physically active (“Attempters”), were already physically active on a regular basis (“Regular Actives”), or had not tried to become more physically active (“Non-Attempters”). Physical activity was measured using the International Physical Activity Questionnaire (IPAQ), and fitness level was assessed as physical working capacity (PWC) via bicycle ergometry. Mixed ANOVAs including Time and Perceived Change as within and between factors were conducted, followed up by simple effect analyses. Results: Participants stating to have become more active in the past six months (Changers) showed a significant increase in vigorous physical activity but not in moderate physical activity, with an average of 6.8 (Study 1) and 10.6 (Study 2) MET-h per week in vigorous activity. Corroborating these findings, objective fitness also significantly increased in the group of Changers. No systematic change in moderate or vigorous physical activity was observed for the three other ‘non-changer’ groups (regular actives, attempters, non-attempters). Conclusion: The intensity of physical activity is the crucial variable for people’s perception of change in physical activity. Moderate physical activity seems not to be perceived as an effective means for behavior change. It thus might fail to unfold sufficient motivational impact, despite its known positive effects on health.